The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1007/s004200050185
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated dibenzo- p -dioxin and dibenzofuran levels and patterns in polyvinylchloride and chloralkali industry workers

Abstract: The production of chlorine and vinyl chloride (VCM) is associated with the formation of polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs). The objective of the present study was to determine whether the levels and congener patterns of PCDDs and PCDFs in the blood of workers involved in the production of such substances could be related to their occupational environment. PCDD and PCDF levels in blood plasma from VCM and chloralkali workers and in referents were determined by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…The production of metallic magnesium is another type of process in which substantial amounts of PCDDs and PCDFs are formed. This is reflected in the congener pattern detected in blood plasma from workers in these plants, where elevated levels of primarily PCDFs were found (Hansson et al 1997). Therefore, the specific study of the different PCDD/F congeners can give information which helps to distinguish between nonoccupational and occupational exposures.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The production of metallic magnesium is another type of process in which substantial amounts of PCDDs and PCDFs are formed. This is reflected in the congener pattern detected in blood plasma from workers in these plants, where elevated levels of primarily PCDFs were found (Hansson et al 1997). Therefore, the specific study of the different PCDD/F congeners can give information which helps to distinguish between nonoccupational and occupational exposures.…”
Section: Discussionmentioning
confidence: 94%
“…The congener 2,3,7,8-TCDD seemed to be increased in people exposed to phenoxy-herbicides (Heederik et al 1998), while the congeners 2,3,7,8-TCDD and 2,3,7, 8-TCDF were increased in pulp-bleaching workers (Schecter et al 1991). In turn, the congeners 1,2, 3,4,6,7,1,2,3,4,7,2,3,6,7, 8-HxCDF were found to be related to work in the vinyl chloride and chloralkali industries (Hansson et al 1997). The production of metallic magnesium is another type of process in which substantial amounts of PCDDs and PCDFs are formed.…”
Section: Discussionmentioning
confidence: 97%
“…For example, 2,3,7,8-tetrachlorodibenzodioxin (TCDD) has been observed to be increased in subjects exposed to phenoxy herbicides (Heederik et al 1998), while the congeners 1,2, 3,4,6,7,2,3,4,7,2,3,6,7,HxCDFs were found to be related to vinyl chloride and chloralkali production (Hansson et al 1997). The production of metallic magnesium is another type of process in which substantial amounts of PCDD and PCDFs are formed.…”
Section: Discussionmentioning
confidence: 97%
“…Workers in the PVC and paper industry, who are commonly exposed to dioxin, are at risk (1.3–5.0). Polychlorinated dibenzo‐ para ‐dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs), which are classified as human carcinogens, are formed in the pyrolysis of PVC, chlorophenol production and paper pulp bleaching with free chlorine 79,80 . In Italy, excess mortality has also been recorded for melanoma in an area previously contaminated by dioxin 81…”
Section: Discussionmentioning
confidence: 99%